Artificial Intelligence in Coronary CT Angiography: Current Status and Future Prospects - Liao, Jiahui; Huang, Lanfang; Qu, Meizi; Chen, Binghui; Wang, Guojie (Frontiers in Cardiovascular Medicine, 2022)
Coronary heart disease (CHD) is the disease with the highest mortality in the world, and the early diagnosis and treatment of CHD should be emphasized. Currently, coronary CT angiography (CCTA) has been the prior choice for CHD screening and diagnosis, but it cannot meet the clinical needs in terms of examination quality, accuracy of reporting and prognosis analysis. In recent years, artificial intelligence (AI) has developed rapidly in the field of medicine, and it played an important role in auxiliary diagnosis, disease mechanism analysis and prognosis assessment, among which there were also a series of studies regarding CHD. In this paper, the application and research status of AI in CCTA was summarized, and the prospects of this field was also described.